EVALUASI KEBIJAKAN PEMUNGUTAN PAJAK KOS KOTA SEMARANG (Studi Pada Dinas Pengelolaan Keuangan Dan Aset Daerah Kota Semarang) - M. Sugiarto; Priyatno Harsasto; Dzunuwanus Manar (Journal of Politic and Government Studies, 2017)
Boarding house tax is a new tax that is placed in the section of hotel tax. According to as potential of Semarang which has attracted migrants who require temporary housing, it is not suprised that many rental on boarding house businesses appear. Boarding house effort on a since a lot of boarding house enacted in Semarang, therefore tax on boarding house was implemented.  Focus of the study is implementation of the policy by using qualitative methods of analytical and descriptive. The study will try to find the widest possible knowledge of by describing and analyzing the research object. The findings of the study shows that the implementation of tax policies boarding house has not run optimally since aspects of the implementation of policies were not adequate. Deficiency lies in lack of technical guidance, human resources (HR) and lack of participation from the taxpayer.  The implementation of Tax policies boarding house  in Semarang Inadequate in order to be succesfully implemented, the existing shortcoming must be fixed. Moreover, improvement of operation away government agencies in Semarang City also important to develop the tax policy. Keywords: Evaluation, Policies, Boarding house tax